Exercise training reduces brainstem oxidative stress and restores normal breathing function in heart failure (vol 172, pg 470, 2021) - Diaz-Jara, Esteban; Diaz, Hugo S.; Rios-Gallardo, Angelica; Ortolani, Domiziana; Andrade, David C.; Toledo, Camilo; V. Pereyra, Katherin; Schwarz, Karla; Ramirez, Gigliola; Ortiz, Fernando C.; Andia, Marcelo E.; Del Rio, Rodrigo (My University, 2022)
<Affiliation d correspond to: Mechanism of Myelin Formation and Repair Laboratory, Instituto de Ciencias Biomédicas, Facultad de Ciencias de Salud, Universidad Autónoma de Chile, Santiago, Chile> <Change to Funding section: We acknowledge Fondo de Desarrollo Científico y Tecnológico Fondecyt [Nº 1180172, Nº 3190659, Nº 3210564 and Nº 1210940], ANID – Millennium Science Initiative Program [ NCN17_129] and the Basal Centre of Excellence in Aging and Regeneration [AFB 170005] of Pontificia Universidad Católica de Chile.> The authors would like to apologize for any inconvenience caused.